PROFILE OF THE DECISION MAKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS ON ECOSYSTEM MATERIALS THROUGH THE DEBATE METHOD - Dadi Rosadi; Noviyanti Noviyanti (Jurnal Pengajaran MIPA, 2021)
The research entitled "Profile of Decision Making Ability of Junior High School Students on Materials Ecosystem Through the Debate Method" aims to determine students' ability to take a decision and the basis for that decision. The method used in this research is descriptive. The research subject is seven grade (VII) academic year 2021/2022 in junior high schools at indonesian school of Kuala Lumpur. Results of research conducted shows that students have been able to choose one alternative from alternative answers which is available. As for the basis for making decisions during debates, students use intuition a lot as a basis for decision making. Another finding obtained at the time of the study was that students become more active, motivated, and more positive about the environment.